Pengaruh persentase CO2 terhadap temperatur dan kecepatan api premixed laminar pada oxy-butane combustion - Lilis Yuliati; Francisca Gayuh Utami Dewi; Ichtiaraka Amarullah (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
Oxy-combustion is one of the technologies developed to reduce the amount of CO2 released into the atmosphere in order to reduce the greenhouse effect and global warming. Gas recirculation in oxy-combustion results in the presence of CO2 in the oxidizer. This study was conducted to determine the effect of the percentage of CO2 on the laminar premixed flame speed in the oxy-butane combustion process. Experiment was conducted on equivalent ratios of 0.6, 0.8, 1, 1.2 and 1.4. CO2 content were varied by 50%, 55%, 60%, 65% and 70%, calculated based on the amount of oxygen in the combustion process. The measurement of laminar premixed flame speed was carried out on a cylindrical tube burner. The results showed that the flame temperature and the laminar premixed flame speed decreased with the increasing of CO2 percentage in the oxidizer. The presence of CO2 causes the heat generated from the combustion process absorbed by CO2, so that the flame temperature is reduced. The decreasing in the flame temperature is an important factor which caused the decreasing in laminar premixed flame speed in a mixture with CO2 content. Furthermore, the presence of CO2 in the reactants prevents the butane and oxygen from mixing and reacting, hence the flame speed becomes lower. In addition, it is known that for every percentage of CO2 in the oxidizer, the flame has a maximum flame temperature and speed at an equivalent ratio of unity.